2015
DOI: 10.1179/1607845415y.0000000033
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of F-18 FDG PET/CT quantization parameters for progression-free survival in patients with diffuse large B-cell lymphoma

Abstract: In contrast to SUVmax, the MTV and TLG may be significant prognostic markers for PFS in DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…MTV, NCCN-IPI and Ann Arbor stage failed to predict survivals independently. Our conclusion is nearly consistent with four retrospective studies respectively conducted by Esfahani, Kim, Ceriani and Xie, in despite of different patient population and different statistical methods [11, 13, 14, 19]. Song and colleagues found MTV as an independent factor of outcome in patients with primary gastrointestinal DLBCL and DLBCL with bone marrow involvement [10, 18].…”
Section: Discussionsupporting
confidence: 90%
“…MTV, NCCN-IPI and Ann Arbor stage failed to predict survivals independently. Our conclusion is nearly consistent with four retrospective studies respectively conducted by Esfahani, Kim, Ceriani and Xie, in despite of different patient population and different statistical methods [11, 13, 14, 19]. Song and colleagues found MTV as an independent factor of outcome in patients with primary gastrointestinal DLBCL and DLBCL with bone marrow involvement [10, 18].…”
Section: Discussionsupporting
confidence: 90%
“…TLG, which combined the volumetric and metabolic information of 18 F-FDG PET, was also calculated in this study. Elevated TLG has also been shown to be associated with poor survival in various types of cancer, but its prognostic value in testicular lymphoma has not been well established [ 30 ]. As a result, we demonstrated that MTV and TLG may greatly differ between different patients.…”
Section: Discussionmentioning
confidence: 99%
“…The same group of investigators found similar results in 165 early-stage (71 % IPI ≤2) primary gastrointestinal DLBCL patients [147]. Likewise, Xie et al demonstrated that according to the cutoff determined from ROC analysis, lower MTV and TLG values prior to therapy were highly predictive of favorable PFS in DLBCL (n = 60) [144]. Multivariate analysis revealed that a high IPI score (p = 0.001) and high MTV (p < 0.001) were independent prognostic factors for both PFS and OS, while other known prognostic factors were not significant.…”
Section: Prognostic Value Of Pet-derived Quantitative Metrics At Basementioning
confidence: 71%
“…Similarly, high MTV and TLG values unfavorably influenced the 3-year OS (OR, 5.40 and 2.19, respectively). Five trials used the old IPI scoring system for risk stratification [137,138,141,143,150], one trial used the age-adjusted IPI scoring system [144], and the other used the recently proposed NCCN-IPI scoring system [146]. Overall this meta-analysis found that the outcomes of the included studies were inconsistent.…”
Section: Prognostic Value Of Pet-derived Quantitative Metrics At Basementioning
confidence: 99%